Amyand's hernia - Kulwant Singh; Rana Ranjit Singh; Sundeep Kaur (Wolters Kluwer Medknow Publications, 2011)
We report two children with Amyand's hernia, where the appendices along with caecum were found within the left hernial sac, which were operated for obstructed inguinal hernia.